Analytic Continuation of Euler Polynomials and the Euler Zeta Function - C. S. Ryoo (Discrete Dynamics in Nature and Society)
We study that the Euler numbers En and Euler polynomials Enz are analytically continued to Es and E(s,w). We investigate the new concept of dynamics of the zeros of analytica continued polynomials. Finally, we observe an interesting phenomenon of “scattering” of the zeros of E(s,w).